Telaah Kurikulum Bahasa Arab di Ma’had Qur’an Rawa Gede Bogor Tahun Pelajaran 2022/2023 - Salwa Syahirah; Sahlani (INTIFA: Journal of Education and Language, 2024)
The aim of this research is to find out the curriculum model used in the BISA Foundation curriculum and the independent Ma'had Qur'an Rawa Gede curriculum and to find out how to implement and evaluate the two curricula in learning Arabic at Ma'had Qur'an Rawa Gede. This research uses a qualitative approach with qualitative descriptive methods and field research. The data analysis technique in this research uses data reduction where the data that the researcher has obtained from observations, interviews and documentation are selected in essence and explained regarding the model, implementation and evaluation of the BISA Foundation curriculum and the independent Ma'had Qur'an Rawa Gede curriculum. which is used in learning Arabic at Ma'had Qur'an Rawa Gede. The validity of the data was carried out through a credibility test using source triangulation and technical triangulation techniques. The results of this research are that the BISA Foundation curriculum model and the independent Ma'had Qur'an Rawa Gede curriculum use the academic subject curriculum model. The implementation of the two curricula in Arabic language learning is viewed in terms of program development where there is annual and daily program development, in terms of the teaching and learning process in the classroom and in terms of evaluating student learning outcomes. Evaluation of the two curricula in Arabic language learning has not been carried out in its entirety at Ma'had Qur'an Rawa Gede.   Abstrak Tujuan penelitian ini adalah untuk mengetahui model kurikulum yang digunakan pada kurikulum Yayasan BISA dan kurikulum mandiri Ma'had Qur'an Rawa Gede dan mengetahui bagaimana implementasi serta evaluasi kedua kurikulum tersebut dalam pembelajaran bahasa Arab di Ma'had Qur'an Rawa Gede. Penelitian ini menggunakan pendekatan kualitatif dengan jenis metode deskriptif kualitatif dan studi lapangan (research field). Teknik analisis data dalam penelitian ini menggunakan reduksi data dimana data yang telah peneliti peroleh dari hasil observasi, wawancara dan dokumentasi dipilih pokok-pokoknya saja dan dijelaskan mengenai model, implementasi, serta evaluasi kurikulum Yayasan BISA dan kurikulum mandiri Ma’had Qur’an Rawa Gede yang digunakan dalam pembelajaran bahasa Arab di Ma’had Qur’an Rawa Gede. Keabsahan data dilakukan melalui uji kreadibilitas dengan menggunakan teknik triangulasi sumber dan triangulasi teknik. Hasil dari penelitian ini bahwasannya model kurikulum Yayasan BISA dan kurikulum mandiri Ma'had Qur'an Rawa Gede menggunakan model kurikulum subjek akademik. Implementasi dari kedua kurikulum tersebut dalam pembelajaran bahasa Arab ditinjau dari segi pengembangan program dimana terdapat pengembangan program tahunan dan harian, dari segi proses belajar mengajar di dalam kelas dan dari segi evaluasi hasil belajar santri. Evaluasi kedua kurikulum tersebut dalam pembelajaran bahasa Arab belum terlaksana secara keseluruhan di Ma'had Qur'an Rawa Gede.